2005
DOI: 10.1007/s00221-005-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Planning and drawing complex shapes

Abstract: Arm and hand movements are generally controlled using a combination of sensory-based and memory-based guidance mechanisms. This study examined similarities and differences in visually-guided and memory-guided arm movements, and sought to determine to what extent certain control principles apply to each type of movement. In particular, the 2/3 power law is a principle that appears to govern the formation o f complex, curved hand trajectories; it specifies that the tangential velocity should be proportional to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Several other recent studies have also reported strong departures from the two-thirds power law [58],[59]; for locomotion, see also [16],[17]. These studies either employed different experimental paradigms from those used here or offered alternative explanations for the observed violations of the power law.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several other recent studies have also reported strong departures from the two-thirds power law [58],[59]; for locomotion, see also [16],[17]. These studies either employed different experimental paradigms from those used here or offered alternative explanations for the observed violations of the power law.…”
Section: Discussionmentioning
confidence: 58%
“…Examining the generation of different patterns of complex figural forms in various tasks and conditions (tracking, drawing from memory, tracing) Flanders et al [59] also showed significant differences in the values of the exponent of the power law depending on the size and orientation of the trajectory. In particular the authors suggested that strategic or cognitive factors affect the relation between hand velocity and curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having emphasised this dissociation, it should be mentioned that there remains a degree of overlap in the neural circuitry controlling externally and internally cued movements. The cerebellum can function during internally cued movements (Mushiake and Strick, 1993) and the basal ganglia and SMA in externally cued movements (Jueptner et al ., 1997a/b; Vaillancourt, Mayka and Corcos, 2006; Vaillancourt, Thulburn and Corcos, 2003). These findings can be explained by the presence of specific sub circuits within the cerebellar and basal ganglia systems that are specific for each movement type and which are superimposed on a background of overlapping functions (Van Donkelaar et al ., 1999;2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous behavioural work has demonstrated differences between tracing and drawing eye-hand coordination with and without visual cues, suggesting that the two forms of movement recruit different brain areas. Flanders, Mrotek and Gielen, (2006) compared the kinematics of tracing a seen shape with subsequent drawing from memory of that shape. They observed highly similar patterns between the two tasks but compared to the tracing task, subjects spent more time in areas of tight curvature during drawing and proposed that this represented a strategy for learning and remembering the shape.…”
Section: Introductionmentioning
confidence: 99%